Implementación de un sistema solar para el calentamiento de agua en uso doméstico - Chochos Hernandez, Darwin Gabriel (2019)
Energy and its use in any of its forms, have delineated the development of human society in each of its evolutionary stages. Trough the years, humanity has perfected the use of energy, going from the simplest to the most complex methods. In the present titling work, the waste of solar energy is analyzed at San Buenaventura parish, and the selection of the solar system that allows to take advantage of it. Considering all these aspects, a water heating system for domestic use is being dimensioned and implemented to replace the conventional one, which selects the parabolic trough solar collector (CCP) and a vacuum tube solar collector (heat pipe), which are: safe, efficient, economical, long-lasting and easy to maintain. For the feasibility of this technological proposal, a solar radiation research is carried out in the sector, receiving an average value of 828 Wh / m2 with peaks greater than 1899 Wh / m2 allowing the sizing of the parabolic trough solar collector (CCP) to jointly with the solar collector of vacuum tubes achieve an average temperature higher than 26 ° C in less time, reaching an efficiency of 35% at a height of 2750 masl, data obtained for the month of February which can be seen in table 5.1. For a better use of the radiation captured in the day by the system, the hot water is stored in a selected accumulator to satisfy the need of 5 people, it has a capacity of 100 liters and keeps the hot water for 24 hours, having a 5% temperature loss, thanks to the thermal insulation layer (polyurethane foam) that allows to minimize the flow of heat to the environment. This type of heating that has a renewable energy source contributes greatly to the environment caring. Keywords: Radiation, solar collector, efficiency, thermal insulation, feasibility.